Current possibilities of pharmacological correction of neuroimmune joint damage in patients with knee osteoarthritis in long COVID conditions - I. V. Sarvilina; I. S. Dydykina; A. M. Lila (Современная ревматология)
Objective: to evaluate the efficacy and safety of the parenteral form of pharmaceutical chondroitin sulfate (CS) in neuroimmune joint damage in patients with early knee osteoarthritis (OA) in long COVID.Patients and methods. An open prospective controlled randomized study was conducted, its duration was 50 days of active controlled therapy. The study included 82 patients (age 57–63 years, men – 29, women – 53) with clinical symptoms of early knee OA and confirmed long COVID type 2 (persistence of symptoms 4–12 weeks after infection with SARS-CoV2). The diagnosis of OA was established in accordance with the updated classification criteria for early knee OA (2018).Patients were randomized into two groups: group 1 – the main group (n=42) and group 2 – control group (n=40). Patients in both groups received celecoxib at a dose of 200 mg with the possibility of reducing the dose to 100 mg or completely discontinuing the drug if necessary. Patients of the 1st group additionally received a parenteral form of CS (Chondroguard® solution for intramuscular and intraarticular administration, 100 mg/ml). At baseline (Day 1) and on the 50th day of the study, pain intensity was assessed in all patients using a visual analogue scale (VAS), the degree of functional impairment (FI) of the joints according to the Lequesne index, ultrasound of the knee joint was performed, CRP, D-dimer, fibrinogen, interleukin (IL) 1β, IL6 levels were studied. The presence of SARS-CoV2 was determined by polymerase chain reaction in scrapings from the mucous membrane of the nasal cavity and oropharynx, and a qualitative proteomic analysis was performed (1-2DE, MALDI-TOF/TOF-MS, PathCards database). The safety of therapy was assessed using the WHO and Naranjo scales.Results and discussion. It was established that CS therapy was well tolerated and was accompanied by a significant decrease in pain intensity according to VAS (U-test=5.71; p<0.0001), in FI according to the Lequesne scale (U-test=6.32; p<0.0001), in manifestations of synovitis and tendinitis in the group treated with CS and celecoxib, compared with the control group. During the treatment by CS a statistically significant (p<0.0001) decrease in the level of pro-inflammatory markers in the blood serum (CRP, IL6, IL1β), D-dimer and fibrinogen was noted. Proteomic analysis showed a decrease in the blood serum of patients of the 1st group of eotaxin 1, IL8, IL15, interferon γ inducible protein 10 levels, and an increase in the expression of nerve fiber growth factor β, an antagonist of the IL1 receptor.Conclusion. The use of pharmaceutical parenteral CS in combination with oral celecoxib in patients with early OA of the knee joint, the clinical signs of which manifested after infection with SARS-CoV2 and persisted in long COVID conditions, contributed to a decrease in the severity of pain and stiffness in the knee joint, as well as improved functional capabilities.